Strategically-framed environmental disclosure index: A measurement approach of Malaysian public listed companies corporate environmental reporting practices - Jaaffar A.H.; Alrazi B.; Ooi S.K.; Shamsuddin A. (Inderscience Publishers, 2023)
Environmental; Environmental reporting; Neo-institutional theories; Organisational; Social and governance; Strategically-framed environmental disclosure index; Environmental management; compliance; environmental policy; governance approach; performance assessment; public service; qualitative analysis; Malaysia